Ekologiczny wymiar niedoskonałości rynku a polityki makroekonomiczne - Rumianowska, Irena (Wydawnictwo Akademii Ekonomicznej im. Oskara Langego we Wrocławiu, 2008)
Market economy in action is characterized by many market imperfections that possess economic,social and ecological scope. Their occurrence forces and rationalizes government intervention into marketmechanism. The aim of this paper is to show the ecological scope of market imperfections, especiallythe occurrence of externalities and a brief introduction into government actions that through environmentalpolicy and macroeconomic policies supplement and correct market mechanism in the area ofrational governance of ecological assets and environmental protection. The fulfillment of environmentalgoals is a domain of environmental policy, however its effectiveness depends on respecting ecologicalaims within basic macroeconomic policies, mainly fiscal policy, trade policy and sector policies - industrialpolicy, energetic policy, transport policy, agricultural policy etc.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2008; nr 1191, s. 556-565